UAV - Digital Terrain Elevation Model (DTM) from Röbäcksdalen Drone area 01 from 2021, 2025-07-09 - Röbäcksdalen Field Research Station (Swedish University of Agricultural Sciences, 2026)
Digital Surface Model generated from photos taken from an UAV platform using photo-stereography techniques. Nominal pixel size is 5 cm.
Röbäcksdalen Field Research Station (2026). UAV - Digital Terrain Elevation Model (DTM) from Röbäcksdalen Drone area 01 from 2021, 2025-07-09 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/Qz357tHm15UyaIVOQSrZYTM7
Keywords: SITES Spectral; Calibration/Validation; Digital Elevation / Digital Surface Models; Ecosystem functions; NDVI; Plant Phenology; Reflectance; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap